PEMANFAATAN VIDEOSCRIBE OLEH GURU PAI: PERSPEKTIF DAN TANTANGAN DALAM PENGAJARAN DI SMK NEGERI 1 EMPAT LAWANG - Abdiyantoro, Restu; Diana Sari, Novita; Kristina, Epa; Rahmi Nasution, Aida (STAI Pelabuhan Ratu, 2025)
This research aims to find out the utilisation of Sparkol VideoScribe by Islamic Education (PAI) teachers at SMK Negeri 1 Empat Lawang in improving student engagement in learning. The background of this research focuses on technological advances that can support the teaching and learning process, where VideoScribe as an innovative tool allows the creation of interactive and visually appealing content. The method used is a qualitative descriptive approach, with data collection through interviews with PAI teachers and analysis of related literature. The results showed that VideoScribe successfully captured students' attention, especially for those with visual learning preferences, despite challenges such as limited projector availability and unstable internet connectivity. The conclusion of this study confirms that while VideoScribe offers great potential to enhance religious education, it is important to address infrastructure and engagement issues for all students to utilise this technological advancement in their learning experience. The implications of this study indicate the need for further support for the integration of technology in education.